PACS2001. Proceedings of the 2001 Particle Accelerator Conference (Cat. No.01CH37268)
DOI: 10.1109/pac.2001.987362
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the low energy demonstration accelerator (LEDA) halo experiment beam instrumentation

Abstract: A 52 quadrupole-magnet FODO lattice has been assembled and operated at the Los Alamos National Laboratory. The purpose of this lattice is to provide a platform to measure the resulting beam halo as the first four magnets of the lattice produce various mismatch conditions. These data are then compared with particle simulations so that halo formation mechanisms may be better understood. The lattice is appended to the LEDA 6.7-MeV radio frequency quadrupole (RFQ) and is followed by a short high-energy beam transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The addition of the attenuator characterization files decreased system error. The calibration test routine showed that the total absolute errors for horizontal and vertical position are well within specified tolerance [1]. …”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The addition of the attenuator characterization files decreased system error. The calibration test routine showed that the total absolute errors for horizontal and vertical position are well within specified tolerance [1]. …”
Section: Discussionmentioning
confidence: 86%
“…First, it provides information that allows the centering of the beam in the HEBT and into the beamstop. Secondly, it allows verification of the quadrupole magnetic field settings by offsetting the beam position from magnetic lattice center [1].…”
Section: Bpm Configuration and Usementioning
confidence: 99%
See 1 more Smart Citation
“…This channel (Fig. 4) contains 52 singlet quadrupole magnets, ten x-y steering magnet pairs, ten stripline beam position monitors, nine x-y beam profile monitors (each unit contains a wire scanner and two halo scrapers as described in [25]), five PMT-based beam-loss monitors, and three AC current toroids [26]. The HS/WS diagnostic device [25] records the beam profile with~10…”
Section: Beam-halo Channel Configurationmentioning
confidence: 99%
“…Several of the problems encountered with that system have been corrected, as well as new capabilities added, with the resultant system being presented here. Currently the LEDA accelerator is configured to conduct a beam halo experiment.Beam diagnostics include fifteen beam position monitors in the 52-quadrupole magnet focusingdefocusing (FODO) lattice, along with wire scanners, beam-loss monitors and current monitors [7]. The nature of the experiment places a requirement for additional dynamic range on the BPM electronics.…”
mentioning
confidence: 99%